State of Corruption : Power, Politics, and Policies in Malaysia (Gerakbudaya Enterprise, 2023)
State of Corruption: Power, Politics, and Policies in Malaysia offers compelling new empirical insights into the covert world of corruption. This book, a collection of three reports, is a penetrating assessment of the controversial, complex, and diverse ties between business and politics that have led to patronage, cronyism, collusion, nepotism, and rent-seeking. A novel assessment is provided of foundations controlled by politicians who abuse them to obtain 'donations' which are then funnelled into the political system, altering fair play during party and general elections. Substantial evidence is provided of the abuse of an ensemble of public policies and government-controlled institutions by politicians to illicitly accumulate wealth. The book also scrutinises a re-emerging phenomenon -- the involvement of business elites in politics as a means to secure power and shape policies. This book's comprehensive, and chilling, examination of systemic corruption in Malaysia is explained in a manner that is accessible to all.